Mechanical stability of airgaps in nano-interconnects. (April 2020) - Vanstreels, K.; Zahedmanesh, H.; Gonzalez, M.
Abstract: In this study the impact of airgaps on the mechanical stability of advanced nano-interconnects is investigated with the focus on chip package interaction related issues. To this aim, the shear microprobing technique is used in combination with post-mortem failure analysis. This study reveals that in the absence of airgaps, the failure is located at the interface where a large elasticity mismatch exists. Furthermore, it was found that the via density and the via distribution across the back-end-of-line (BEOL) have a clear impact on the force to initiate and grow cracks. The introduction of airgaps into nano-interconnects leads to a shift in the fracture location towards the interface where the airgaps are located, while the relative changes in the amount of failures are explained in terms of the via density and the specific location and geometry of the airgap structures. This work may serve as a guideline to further enhance the mechanical integrity of BEOL airgap technology for future nodes.